Heart failure as an adverse effect of infliximab for Crohn's disease: A case report and review of the literature - Grillo, Thais Gagno [UNESP]; Almeida, Luciana Rocha [UNESP]; Beraldo, Rodrigo Fedatto [UNESP]; Marcondes, Mariana Barros [UNESP]; Rios Queiroz, Diego Aparecido [UNESP]; Silva, Daniel Luiz da [UNESP]; Quera, Rodrigo; Baima, Julio Pinheiro [UNESP]; Saad-Hossne, Rogerio [UNESP]; Sassaki, Ligia Yukie [UNESP] (Baishideng Publishing Group Inc, 2021)
BACKGROUND Anti-tumor necrosis factor agents were the first biologic therapy approved for the management of Crohn's disease (CD). Heart failure (HF) is a rare but potential adverse effect of these medications. The objective of this report is to describe a patient- with CD who developed HF after the use of infliximab. CASE SUMMARY A 50-year-old woman with a history of hypertension and diabetes presented with abdominal pain, diarrhea, and weight loss. Colonoscopy and enterotomography showed ulcerations, areas of stenosis and dilation in the terminal ileum, and thickening of the intestinal wall. The patient underwent ileocolectomy and the surgical specimen confirmed the diagnosis of stenosing CD. The patient started inflixirnab and azathioprine treatment to prevent post -surgical recurrence. At 6 mo after initiating infliximab therapy, the patient complained of dyspnea, Or tho pima, and paroxysmal nocturnal dyspnea that gradually worsened. Echocardiography revealed hiventricular dysfunction, moderate cardiac insufficiency, an ejection fraction of 36%, and moderate pericardial effusion, consistent with HF. The cardiac disease was considered an infliximab adverse effect and the drug was discontinued. The patient received treatment with diuretics for HF and showed improvement of symptoms and cardiac function. Currently, the patient is using anti -in erleukin for CD and is asymptoma CONCLUSION This reported case supports the need to investigate risk factors for HF in inflammatory bowel disease patients and to consider the risk -benefit of introducing infliximab therapy in such patients presenting with HF risk factors.
Keywords: Heart failure; infliximab; Anti tumor necrosis factor therapy; Crohn's disease; inflammatory bowel disease; Case report